Environmental phenols and pubertal development in girls. (November 2015) - Wolff, Mary S.; Teitelbaum, Susan L.; McGovern, Kathleen; Pinney, Susan M.; Windham, Gayle C.; Galvez, Maida; Pajak, Ashley; Rybak, Michael; Calafat, Antonia M.; Kushi, Lawrence H.; Biro, Frank M.; ,
Abstract: Environmental exposures to many phenols are documented worldwide and exposures can be quite high (> 1 μM of urine metabolites). Phenols have a range of hormonal activity, but knowledge of effects on child reproductive development is limited, coming mostly from cross-sectional studies. We undertook a prospective study of pubertal development among 1239 girls recruited at three U.S. sites when they were 6–8 years old and were followed annually for 7 years to determine age at first breast or pubic hair development. Ten phenols were measured in urine collected at enrollment (benzophenone-3, enterolactone, bisphenol A, three parabens (methyl-, ethyl-, propyl-), 2, 5-dichlorophenol, triclosan, genistein, daidzein). We used multivariable adjusted Cox proportional hazards ratios (HR (95% confidence intervals)) and Kaplan–Meier survival analyses to estimate relative risk of earlier or later age at puberty associated with phenol exposures. For enterolactone and benzophenone-3, girls experienced breast development 5–6 months later, adjusted HR 0.79 (0.64–0.98) and HR 0.80 (0.65–0.98) respectively for the 5th vs 1st quintiles of urinary biomarkers (μg/g-creatinine). Earlier breast development was seen for triclosan and 2, 5-dichlorophenol: 4–9 months sooner for 5th vs 1st quintiles of urinary concentrations (HR 1.17 (0.96–1.43) and HR 1.37 (1.09–1.72), respectively). Association of breast development with enterolactone, but not the other three phenols, was mediated by body size. These phenols may be antiadipogens (benzophenone-3 and enterolactone) or thyroid agonists (triclosan and 2, 5-dichlorophenol), and their ubiquity and relatively high levels in children would benefit from further investigation to confirm these findings and to establish whether there are certain windows of susceptibility during which exposure can affect pubertal development. Highlights: Phenols are associated with timing of breast and pubic hair development in girls. Associations suggest earlier or later pubertal development for different phenols. Associations of phenols with breast development may be mediated by body size. Associations may differ for different timeframes of the developmental window.